2006
DOI: 10.1093/jpepsy/jsj123
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Early Onset Asthma and Wheezing in a Healthy Birth Cohort of 2- to 3-Year Olds

Abstract: Findings confirm and extend previous work documenting demographic risks and highlight smoking, violent events, and social support in early onset asthma and wheezing. Findings illustrate the need for ecologically based interventions to treat asthma and wheezing in young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
55
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 40 publications
10
55
0
Order By: Relevance
“…Various studies in the last decade, the majority of which in the United States, identified an association between community violence and asthma 8,9,10,11,12,20 . Although the studies analyzed different outcomes, like hospitalizations and occurrence and number of days with symptoms, besides distinct contexts, they showed a similar association to that found in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various studies in the last decade, the majority of which in the United States, identified an association between community violence and asthma 8,9,10,11,12,20 . Although the studies analyzed different outcomes, like hospitalizations and occurrence and number of days with symptoms, besides distinct contexts, they showed a similar association to that found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the independent variable "community violence" was not measured directly with a specific instrument. The majority of the studies on the theme have found that exposure to a violent act such as being assaulted or witnessing a fight involving firearms or knives is already representative of the community violence phenomenon 8,9,10,11,12,20 . When the SCAALA project was designed, there were no validated indicators for measuring this phenomenon in the Brazilian population, or for Table 2 Logistic regression between items on community violence and presence of asthma symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among 851 low-income children, increased exposure to community violence was associated with a higher number of daytime and nighttime asthma symptoms (7). In a birth cohort study, violence exposure was associated with an increased risk of wheezing at age 2-3 years (25).…”
Section: Discussionmentioning
confidence: 99%